Case Report: Whole genome sequencing identifies a novel deep intronic COL4A5 variant of uncertain significance in X-linked Alport syndrome - Kim, Hoon Seok; Kim, Myungshin; Suh, Jin-Soon; Lee, Yeonhee (Frontiers in Pediatrics, 2025)
Diagnosing Alport syndrome can be particularly challenging when targeted sequencing methods, such as panel-based next-generation sequencing (NGS), fail to identify pathogenic variants, especially deep intronic mutations. The syndrome is caused by mutations in type IV collagen genes (COL4A3, COL4A4, or COL4A5), with X-linked Alport syndrome (XLAS) accounting for approximately 80% of cases. Here, we report the case of a 4-year-old boy who presented with persistent microscopic hematuria detected during routine urinalysis. Although renal ultrasonography showed mild bilateral medullary nephrocalcinosis, no proteinuria was observed. His mother had been previously diagnosed with Alport syndrome by renal biopsy, but prior targeted sequencing failed to identify any disease-causing variants. To avoid an invasive renal biopsy in this pediatric patient, we directly performed whole genome sequencing (WGS), identifying a novel deep intronic hemizygous variant in the COL4A5 gene (c.2395 + 2723T > G). This variant, classified as a variant of uncertain significance (VUS) according to ACMG-AMP guidelines, was confirmed by Sanger sequencing to be hemizygous in the patient and heterozygous in his mother. The patient currently maintains normal renal function, vision, and hearing, with only microscopic hematuria persisting. This case highlights the diagnostic challenges posed by deep intronic variants in XLAS and demonstrates the clinical utility of WGS in cases where conventional genetic testing is inconclusive. Early genetic diagnosis facilitated timely intervention without requiring invasive procedures, emphasizing the growing role of comprehensive genomic sequencing in uncovering elusive genetic variants in clinically suspected Alport syndrome.